Cognitive-behavioral intervention for math anxiety in childhood: a case report - Amanda Paola Lobo Guimarães; Vitor Geraldi Haase; Carmen Beatriz Neufeld (Dementia & Neuropsychologia, 2021)
ABSTRACT Math anxiety (MA) is a feeling of dread, tension and anxiety when dealing with math situations. Avoidance behavior prevents children from learning math, impairing their performance. Cognitive behavioral therapy is an approach with robust evidence of efficacy in treating anxiety disorders. The Coping Cat, a protocol for treating anxiety disorders, inspired the MA intervention reported here. The participant was N. L., an 11-year-old female displaying math-related and math-unrelated anxiety symptoms. Outcome measures included arithmetic performance, and self-reports of general positive and negative affect and math-related self-perceived performance, attitude, unhappiness and anxiety. The therapeutic approach included psychoeducation, relaxation, diaphragmatic breathing, cognitive restructuring, problem-solving training and graded exposure. After 12 individual intervention sessions, there was an improvement in negative and positive affect, as well as an improvement in self-perceived performance and a decrease in MA.